Low-Power and Topology-Free Data Transfer Protocol with Synchronous Packet Transmissions - Jeong, Jongsoo; Park, Jongjun; Jeong, Hoon; Jun, JongArm; Liang, Chieh-Jan Mike; Ko, JeongGil (SECON (Internation Conference on Sensing, Communication, and Networking), 2014)
Tightly synchronizing transmissions of the same packet from different sources theoretically results in constructive interference. Exploiting this property potentially speeds up network-wide packet propagation with minimal latencies. Our empirical results suggest the timing constraints can be relaxed in the real world, especially for radios using lower frequencies such as the IEEE 802.15.4 radios at 900 MHz. Based on these observations we propose PEASST, a topology-free protocol that leverages synchronized transmissions to lower the cost of end-to-end data transfers, and enables multiple traffic flows. In addition, PEASST integrates a receiver-initiated duty-cycling mechanism to further reduce node energy consumption. Results from both our Matlab-based simulations and indoor testbed reveal that PEASST can achieve a packet delivery latency matching the current state-of-the-art schemes that also leverages synchronized transmissions. In addition, PEASST reduces the radio duty-cycling by three-fold. Furthermore, comparisons with a multihop routing protocol shows that PEASST effectively reduces the per-packet control overhead. This translates to a 10% higher packet delivery performance with a duty cycle of less than half.